BUILDING SELF-EFFICACY FOR REPRODUCTIVE HEALTH AMONG INDONESIAN MIGRANT WORKERS' CHILDREN IN MALAYSIA: AN ASSET-BASED, GAME-SUPPORTED COMMUNITY PROGRAMME - Ponidi Ponidi; Tika Dewi; Apriliani Apriliani; Rani Suraya; Prima Yanti Siregar; Muhammad Rezebri; Putra Apriadi Siregar (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
Background: Indonesian migrant workers' children in Malaysia face restricted access to formal schooling and reproductive-health (SRH) information. Objective: To design and implement a community-based SRH programme that builds children's self-efficacy using an Asset-Based Community Development (ABCD) approach supported by educational gaming. Methods: A community programme at El Shaddai Learning Centre (Kuala Lumpur) engaged 30 children (7-14 years). The ABCD cycle (discover-dream-design-deliver) informed asset mapping, shared visioning, co-designed content, and delivery/evaluation. The intervention comprised age-appropriate interactive talks and a cause-and-effect “snakes-and-ladders” board game. Formative and summative assessments (structured observation, brief oral quizzes) captured SRH understanding and early self-efficacy indicators. Results: Relative to baseline, participants demonstrated improved ability to define SRH, identify age-appropriate protective behaviours, and articulate consequences of risky choices. Early self-efficacy signals (e.g., refusal of unsafe invitations; concrete steps to maintain personal boundaries) were evident during group work and gameplay. Conclusions: An ABCD-anchored, game-supported format is feasible and acceptable in migrant settings. Sustainability should leverage peer-education, youth-friendly referrals, and light process indicators for ongoing monitoring.